Martin Heidegger. Parte seconda - Matussek, Peter; Matussek, Paul (Il sogno della farfalla, 2010)
The essay on the German philosopher Martin Heidegger is part of a larger work, Analytische Psychosentherapie, by Paul Matussek, in which the author sets out to illustrate some of the theoretical assumptions elaborated during his long activity as director of the Research Unit “Psicopathology and psychotherapy” at the Istitute Max Planck in Munich. On the basis of these, each psychic disorder would be characterized by an imbalance between the two aspects of the private ego (privates Selbst) and of the public ego (öffentliches Selbst), where the prevalent interest in the private ego is manifested in depressive disorders. Vice-versa, the excessive investment in the public ego in the face of a private ego which is empty and deficient leads to a disorder of a schizophrenic type, as in the case of Heidegger who is considered an example of a similar pathology (Modellfall). Utilizing the three forms of failed existence theorized by Ludwig Binswanger (mannerism, eccentricity, extravagance), the life of the philosopher is traced highlighting the mechanisms that led him to an extravagant ambition and to a “secrecy”, managing to impose an admiring distance between himself and the others that prevented him from falling into a manifest psychosis. In the essay, co-written with his son Peter, Matussek explores the role that the problematic structure of Heidegger’s personality played on his very philosophical works, in the conviction that this cannot be separated from biographical elements.